Reducing project related uncertainty in "the fuzzy front end" of innovation: A comparison of German and Japanese product innovation projects - Cornelius Herstatt; Birgit Verworn; Akio Nagahira (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2003)
In this paper, we are going to report on the results of an exploratory piece of research about the typical front-end-related activities in 28 innovation projects carried out by 14 German and 13 Japanese companies to reduce project uncertainty. In all cases we observed a range of activities to reduce project specific risks and revealed differences in the practice of innovation management in both the German and Japanese companies. We interviewed managers of 13 Japanese and 14 German enterprises concerning 14 Japanese and 14 German New Product Development projects. The focus of our research was the so called fuzzy front end ;, activities and typical deliverables in the innovation process which might be affected by front end management practice. Overall, in the case of the German as well as the Japanese projects, the uncertainties affected by the market or technology could successfully be reduced during the fuzzy front end and the majority of projects achieved their objectives and efficiency targets. Nevertheless, our study revealed differences in the way such uncertainties were reduced by the companies in Japan and Germany. Generally speaking, the 14 Japanese projects relied on a thorough planning, delegation of front end activities and strict controlling mechanisms to minimize deviations from front end specifications later in the innovation process and hence, achieved efficiency. In contrast, in the majority of the 14 German projects we could neither observe such a formal planning nor such an intensive controlling procedure supported by methods and tools as in the case of the Japanese projects. Instead, the companies in our German sample integrated relevant functions like R&D, marketing, sales, production or customer service from the beginning of the innovation process, usually already during the idea generation phase, to ensure that all critical information and perspectives were taken into consideration right from the beginning, to reduce uncertainties and later deviations as well as enhancing efficiency. Responsibilities were assigned during the fuzzy front end and rarely changed during the implementation of the project.
urn:nbn:de:gbv:830-opus-1467
Keywords: 650; Fuzzy front end; innovation risk; uncertainty; idea generation; project selection; project planning; Japan; Germany